Analysis of Omega-3, AA, EPA, Omega-6, DHA, Pb and Hg Fatty Acid Levels of Sardinella Lemuru - Pertiwi, Estuasih Dyah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose : Lemuru fish has been consumed as fresh fish and raw materials for making pindang fish (steam), canned fish and fish meal by several fishing industries. This is because the price of lemuru fish is relatively cheap but has a high protein content. The high content of omega-3 fatty acids and the incompatibility of the texture of lemuru fish become easily damaged and decayed due to microbiological activity. Therefore, it is necessary to carry out intensive handling both by direct processing in the form of lemuru presto fish and preservation in the form of lemuru fish meal. Methodology : This study is experimental, which aims to analyze the levels of omega-3, AA, EPA, omega-6, and DHA fatty acids using the GC method. Pb and Hg levels using the ICP OES method. The samples of this study were lemuru presto fish and lemuru fish meal. Descriptive data processing using Microsoft Excel 2010 is presented in texttular and tabular form. Results: Lemuru presto fish and lemuru fish meal are highest in omega-3 levels (870.2 and 1714.4 mg/100 g) and DHA levels (713.2 and 1274.0 mg/100 g). The fatty acid content of lemuru fish meal is higher than that of lemuru presto fish. Lemuru fish is safe to consume because its Pb and Hg levels are almost undetectable.